COMPARATIVE ANALYSIS OF TRANSLATIONS PREPARED BY STUDENTS WITH AND WITHOUT LEGAL QUALIFICATIONS - LESZNYÁK, Márta; BALOGH, Dorka (Comparative Legilinguistics, 2019)
In our paper, we present the results of the second phase of a study conducted in collaboration between two higher education institutions in Hungary with different types of translator training: a postgraduate (MA) course at the University of Szeged (SZTE), Faculty of Arts, and a postgraduate specialist training course at Pázmány Péter Catholic University, Budapest (PPKE JÁK), Faculty of Law and Political Sciences. At SZTE, students do not have any legal qualifications, while at PPKE JÁK, students are all qualified legal professionals. Our main research question was whether there are significant differences in the quality of legal translations carried out by students with and without legal qualifications. We analyzed and evaluated the global (holistic) quality of the translations using a five-point scale as suggested by Kiraly (1995: 83), and compared types of errors made by the two groups of students with the help of a special error typology. Our results show that students with legal qualifications perform better in terms of both global and analytic indicators, with significantly less errors made in information transfer and in legal register.